Regulation of Plant Microprocessor Function in Shaping microRNA Landscape - Dolata, Jakub; Taube, Michał; Bajczyk, Mateusz; Jarmolowski, Artur; Szweykowska-Kulinska, Zofia; Bielewicz, Dawid (Frontiers in Plant Science, 2018)
MicroRNAs are small molecules (~21 nucleotides long) that are key regulators of gene expression. They originate from long stem-loop RNAs as a product of cleavage by a protein complex called Microprocessor. The core components of the plant Microprocessor are the RNase type III enzyme Dicer-Like 1 (DCL1), the zinc finger protein Serrate (SE), and the double-stranded RNA binding protein Hyponastic Leaves 1 (HYL1). Microprocessor assembly and its processing of microRNA precursors have been reported to occur in discrete nuclear bodies called Dicing bodies. The accessibility of and modifications to Microprocessor components affect microRNA levels and may have dramatic consequences in plant development. Currently, numerous lines of evidence indicate that plant Microprocessor activity is tightly regulated. The cellular localization of HYL1 is dependent on a specific KETCH1 importin, and the E3 ubiquitin ligase COP1 indirectly protects HYL1 from degradation in a light-dependent manner. Furthermore, proper localization of HYL1 in Dicing bodies is regulated by MOS2. On the other hand, the Dicing body localization of DCL1 is regulated by NOT2b, which also interacts with SE in the nucleus. Posttranslational modifications are substantial factors that contribute to protein functional diversity and provide a fine-tuning system for the regulation of protein activity. The phosphorylation status of HYL1 is crucial for its activity/stability and is a result of the interplay between kinases (MPK3 and SnRK2) and phosphatases (CPL1 and PP4). Additionally, MPK3 and SnRK2 are known to phosphorylate SE. Several other proteins (e.g., TGH, CDF2, SIC, and RCF3) that interact with Microprocessor have been found to influence its RNA-binding and processing activities. In this minireview, recent findings on the various modes of Microprocessor activity regulation are discussed.